Electrostatic restacking of two-dimensional materials to generate novel hetero-superlattices and their energy applications - K. Pramoda; C. N. R. Rao (APL Materials, 2023)
Among the 2D materials, van der Waals heterostructures formed by vertically placing a monolayer of one 2D material over a single layer of another 2D material are gaining importance. As an alternative to such structures, ladder-like networks composed of two different 2D materials with an alternate arrangement of heterolayers can be generated by an electrostatic restacking strategy. The electrostatic restacking of 2D materials is achieved a great success. Various 2D/2D hetero-superlattices reported in the literature are MoS2/graphene, MnO2/Ti3C2, Ti3C2/graphene, NiAl–layered double hydroxides (LDHs)/graphene, and NiAl–LDHs/Ti3C2. The electrostatic restacking of different 2D materials generates novel 2D/2D hetero-superlattices. These hetero-superlattices display interesting electrocatalytic properties as supercapacitor electrodes, for water splitting reactions, as well as a noteworthy activity as cathode materials in lithium/sodium ion batteries. Ladder-like 3D networks of heterolayers obtained by phase-to-phase restacking improve charge-transfer interactions and the accessible area between active sites and electrolyte, thereby showing a higher electrocatalytic activity. The volumetric energy density of 32.6 Wh L−1 obtained with Ti3C2/graphene as a supercapacitor electrode is the highest reported among carbon-based materials. While the BCN/MoS2 superlattice shows a hydrogen evolution reaction (HER) activity comparable to Pt/C, unilamellar metallic MoS2/graphene and MnO2/graphene hetero-superlattices are reported to be efficient for both HER and sodium storage. The ambient instability of various 2D materials under electrocatalytic environments can be improved either by surface-functionalization or by forming hetero-superlattices.